A STUDY CONCERNING OPEN INNOVATION AND ITS RELATION TO INNOVATION AND MARKET ORIENTATION - Santos, Marcia Amorim; Zilber, Moisés Ari; Toledo, Luciano Augusto (Future Studies Research Journal: Trends and Strategies, 2012)
Many global companies, which are proactive to continuous changes in the market so as to access complementary assets, satisfy customers, pursue growth and sustainable competitive advantage, are practicing open innovation, a new paradigm that uses techniques and tools for the development of an innovative collaboration network. Furthermore, there are studies suggesting that companies ought to be market-driven so innovation might be successful. Therefore, this research sought to contribute with the scientific body by addressing the new open innovation paradigm (Chesbrough, 2003) and the widespread strategy of market orientation in the field of innovation. To this effect, we sought to determine whether there is positive correlation between open innovation, innovation and market orientation based on Jaworski and Kohli´s (1993) three pillars. The empirical study was conducted by means of a quantitative survey with the application of a questionnaire at different corporate functional levels. To treat data, we adopted the Spearman´s statistical correlation method. Results linked to the theoretical framework demonstrated that innovation is related to market orientation, but this in turn has no significant relationship with open innovation. It was also verified that there is a deficiency in the generation and dissemination of intelligence, which are fundamental for the correlation between market orientation and open innovation.